Comparative analysis of the red-complex organisms and recently identified periodontal pathogens in the subgingival plaque of diabetic and nondiabetic patients with severe chronic periodontitis - Divya Shree Pandian; Dhayanad John Victor; Priyanka Cholan; P SG Prakash; Sangeetha Subramanian; Sumi Priyadarshini Shankar (Wolters Kluwer Medknow Publications, 2023)
Aim: This analytical case-control study sought to evaluate the presence of the recently established putative periodontal pathogen organisms, Filifactor alocis and Fretibacterium fastidiosum, against the levels of the already established red-complex pathogens, Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola, in chronic periodontitis sites of patients with and without diabetes mellitus. Materials and Methods: Fifty-six subgingival plaque samples were obtained from the deepest sites of subjects diagnosed with severe chronic periodontitis with and without diabetes mellitus. These patients were categorized into two groups of 28 each. Clinical parameters were recorded and microbial analysis was done with quantitative polymerase chain reaction, and the bacterial counts of F. alocis and F. fastidiosum were determined and then compared with that of the red-complex organisms. Results: The bacterial counts were found to be higher in the diabetic group than that in the nondiabetic group, which was statistically significant for T. forsythia (P < 0.037) and T. denticola (P < 0.003). The study found very less number of F. alocis, which was slightly higher in the diabetic group. When correlating the bacterial levels within the nondiabetic groups, the red complex species had a strong positive correlation both individually with F. alocis (P < 0.0001) and F. fastidiosum (P < 0.001) and also when the newer species was clubbed together as a cohort (P < 0.0001). Whereas, in the diabetic group, although there was a positive correlation, there was no statistical significance. Conclusion: The results of this study highlighted the presence of a definite difference in the subgingival microbiota of both the patient groups evaluated. They also indicate that of the newly identified microorganisms, both the cohorts had higher levels of F. fastidiosum, suggesting a pathobiont-like role of this bacteria among both these periodontitis groups. F. alocis was comparatively lesser in number among the cohorts evaluated, and the cause for this decreased level of F. alocis needs to be further evaluated. The results of the present study depict a higher bacterial load in the diabetic group when compared to the nondiabetic group. Further, the study demonstrates a strong correlation between the red-complex species and the newer organisms in the nondiabetic group.